Optical simulation of various phenomena in curved space on photonic chips. Issue 1 (31st December 2023) - Sheng, Chong; Zhu, Shining; Liu, Hui
ABSTRACT: Transformation optics have been an essential paradigm to manipulate electromagnetic waves on the subwavelength scale and have brought various functional photonic architectures into integrated photonic chips. On the other hand, in the spirit of analogical thinking, classical and quantum simulations of general relativity have been extensively studied in diverse physical systems. In this review, we summarize recent advances in analogical gravitation based on integrated photonic chips with the aid of transformation optics. Meanwhile, different types of transformation optical structures, such as gradient waveguides, metasurface waveguides, waveguides on curved space and gradient waveguide arrays, emulating a variety of phenomena in curved space are reviewed, including the gravitational lensing of black holes, Einstein rings, cosmic strings, the particle pair evolution near the event horizon and so on. Furthermore, perspectives for the study of analogical gravitation based on integrated photonic chips are discussed. Graphical Abstract: f3532d0dd-07ba_6